PRODUCTION PATTERNS OF SHEEP AND GOATS IN DISTRICT QILA ABDULLAH (BALOCHISTAN) - Kakar; Z.; I. Ali; Kausarzeb; Z. A. Shah; I. U. Haq; Rafiuallah; T. Hussain; S. Khan (Journal of Animal and Plant Sciences, 2013)
In order to determine the production patterns of sheep and goats the study was carried out during 2005 in five areas of District Qila Abdullah (Balochistan) i.e. Chaman, Qilla Abdullah, PirAlizai, Gulistan and Maizaiadda, where mostly the flocks comprised of Bibrik, Balochi and Dumbi sheep breeds and Kamori, Jatan, Lehri and Khurasani goat breeds. The results showed that the capital cost on animal averaged Rs. 450, while feeding cost was Rs. 3079, medication and vaccination charges Rs. 26, labor charges Rs.135, marketing charges Rs.16 and miscellaneous charges Rs. 9 to accumulate overall per animal recurring cost Rs. 3264.65 per animal/year. Producers received gross revenue of Rs. 5252 from the sale of animals, manure and wool/hair against an expenditure Rs. 3824, hence the net returns came to Rs. 1428 per animal. The farmer earned Rs. 1.38 (1:1.38) on one rupee investment. Breakdown of consumer’s rupee revealed that producer shared 68 paisa from consumer’s rupee and pocketed Rs.0.38 against the cost of one rupee. The cost benefit ratio (average 0.43) in Chaman, Qila Abdullah, PirAlizai, Gulistan and Maizaiadda was 1:0.52, 1:0.39, 1:0.41, 1:0.36 and 1:0.44, respectively. The findings of the study showed that sheep and goat farming is a profitable business in the Balochistan province, especially Qila Abdulla district.
Keywords: Sheep; Goats; production patterns; recurring costs; investment; gross revenue; net income